Jim Johnson, Trumpet, Faculty Artists Recital - Johnson, Jim; Dirks, Rachel; Arrington, Amanda (Kansas State University; School of Music, Theater and Dance, 2018)
Tuesday, August 21st, 2018 7:30 p.m. All Faiths Chapel Philip Sparke - Song and Dance Roy Milligan - Dreams of Karen Joy Webb - Share My Yoke Tamir Akta - Hope and Toronto Billy Joel - Lullaby (Goodnight My Angel)